Hypertrophic obstructive cardiomyopathy with left ventricle outflow tract chordae insertion: Surgery or alcohol septal ablation? A case report - Rania Hammami; Amine Kammoun; Majed Hassine; Tarek Ellouze; Rania Gargouri; Leila Abid (Clinical Case Reports, 2023)
Key Clinical Message Anomalous insertion of chordae is a rare disease that could be associated with hypertrophic obstructive cardiomyopathy (HOCM), but clinical and echocardiographic diagnoses tend to be delayed. Alcohol septal ablation has emerged as an alternative to surgical myomectomy in HOCM. When a patient showed an anomalous insertion of chordae, physicians generally opt for surgery and not alcohol septal ablation. In this report, we present the case of a lady, with symptomatic HOCM associated with a chord inserted on the left ventricular outflow tract. We succeeded to relieve obstruction by alcohol septal ablation without the need for surgery.